2017
DOI: 10.1007/jhep12(2017)012
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic corrections to light-cone distribution amplitudes of S-wave Bc mesons and heavy quarkonia

Abstract: In collinear factorization, light-cone distribution amplitudes (LCDAs) are key ingredients to calculate the production rate of a hadron in high energy exclusive processes. For a doubly-heavy meson system (such as B c , J/ψ, Υ etc), the LCDAs contain perturbative scales that can be integrated out and then are re-factorized into products of perturbatively calculable distribution parts and non-relativistic QCD matrix elements. In this re-factorization scheme, the LCDAs are known at next-to-leading order in the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…In our numerical calculation, we adopt the following input parameters [12,25,32,40,41]: Table I, and in Table II we show the result of the branching fractions for B c → X cc K decays. The branching fractions for B c → ψð3770ÞK decay are displayed in Table V, which contains two sets of S-D mixing angles.…”
Section: Numerical Evaluation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our numerical calculation, we adopt the following input parameters [12,25,32,40,41]: Table I, and in Table II we show the result of the branching fractions for B c → X cc K decays. The branching fractions for B c → ψð3770ÞK decay are displayed in Table V, which contains two sets of S-D mixing angles.…”
Section: Numerical Evaluation and Discussionmentioning
confidence: 99%
“…In Ref. [25], the authors have calculated the relativistic corrections of Gegenbauer moments and found that they are comparable with the next to leading order radiative corrections, and they have also given the total correction values for the first two Gegenbauer moments a 1 and a 2 , which contain leading order contribution, one-loop QCD radiative corrections, and relativistic corrections.…”
Section: Theoretical Frame and The Wave Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…(16), we have (18) where the last term is the same as the one-loop correction of decay constant. By eliminating this term one will arrive at the result for LCDA, which was firstly calculated by Bell and Feldmann [19] and later further explored in NRQCD re-factorization approach [35,36].…”
Section: One-loop Correction To Qcd Operatormentioning
confidence: 99%
“…On the other hand in heavy quarkonium the LCDA and short-distance part of the decay constant are perturbatively calculable by matching QCD onto NRQCD amplitude. Their one-loop correction was obtained in [14] and the relativistic correction was obtained in [26,37]. We treat v 2 and α s corrections are of the same size and expand up to the same power.…”
Section: Light-cone Distribution Amplitudementioning
confidence: 99%